An efficient method to capture the impact of total knee replacement on a variety of simulated patient types: A finite element study. Issue 9 (September 2016) - Conlisk, Noel; Howie, Colin R.; Pankaj, Pankaj
Highlights: A novel method to generate femur models incorporating ageing and osteoporosis is presented. Application of this method to pre- and post-knee arthroplasty scenarios is then considered. Stresses in the anterior region of the femoral cortex increase significantly post-implantation. Stresses in the periprosthetic region increase dramatically with both ageing and thinning. These findings help explain why old osteoporotic patients are at greater risk of fracture. Abstract: Osteoporosis resulting in a reduction in bone stiffness and thinning of the cortex is almost universal in older patients. In this study a novel method to generate computational models of the distal femur which incorporate the effects of ageing and endosteal trabecularisation are presented. Application of this method to pre- and post-knee arthroplasty scenarios is then considered. These computational methods are found to provide a simple yet effective tool for assessing the post-arthroplasty mechanical environment in the knee for different patient types and can help evaluate vulnerability to supracondylar periprosthetic fracture following implantation. Our results show that the stresses in the periprosthetic region increase dramatically with ageing; this is particularly true for higher flexion angles. Stresses in the anterior region of the femoral cortex were also found to increase significantly post-implantation. The most dramatic increases in stresses and strains at these locations were observed in old osteoporotic patients, explaining why this patient group in particular is at greater risk of periprosthetic fractures.